Structuring forces of intertidal infaunal communities on the northern coast of British Columbia, Canada: assessing the relative importance of top-down, bottom-up, middle-out, and abiotic variables - Travis G. Gerwing; Lily Campbell; Diana J. Hamilton; Myriam A. Barbeau; Gregory S. Norris; Sarah E. Dudas; Francis Juanes (Canadian Science Publishing, 2023)
While trophic and habitat-related abiotic variables (predation, competition, tolerance, etc.) are known to influence community structure in many ecosystems, some systems appear to be only minimally influenced by these variables. Sampling multiple tidal flat communities in northern BC, Canada, we investigated the relative importance of top-down and middle-out (mesopredators) variables, competition for resources (bottom up), and abiotic variables in structuring an infaunal community (invertebrates living in sediment). Similar to previous studies on mudflats in the Bay of Fundy (also at a north temperate latitude), we determined that these variables accounted for a minor (0%-9%) proportion of the observed variation in this infaunal community, suggesting that these variables play a small role in structuring this community. Based on the results of our study and in combination with previous experiments on infaunal recovery patterns post disturbance, we posit that the main factors influencing these infaunal communities likely operate at a scale of sites (kilometres) and(or) plot (metres or less) but not transects (10-100 m within site). Candidate forces structuring these intertidal communities that need future examination include regional species pools and the variables that affect these pools, sediment biogeochemistry, and disturbance/recovery history of a site. The similarity of our Pacific coast findings to those from the north temperate Atlantic coast suggests some similarity in the processes structuring these distinct infaunal communities.